1978
DOI: 10.2307/145253
|View full text |Cite
|
Sign up to set email alerts
|

Physician Participation in State Medicaid Programs

Abstract: Medicaid requires that physicians who accept Medicaid reimbursement for treating a patient agree to accept its payment as payment in full. Policy instruments under Medicaid's control are both levels of reimbursement and various administrative burdens imposed on physicians by the program. A model depicting the physician's participation decision is developed, and predictions from the comparative statics analysis are discussed. Data came from a 1975--76 survey of fee-for-service physicians. The results indicate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
142
0

Year Published

1980
1980
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(150 citation statements)
references
References 7 publications
8
142
0
Order By: Relevance
“…Several studies have found significant positive correlations between relative Medicaid fees and both Medicaid participation and caseloads among office-based physicians in general (Sloan, Mitchell, and Cromwell 1978;Hadley 1979;Held and Holahan 1985;Mitchell 1991;Adams 1994) and pediatricians in particular (Perloff, Kletke, and Neckerman 1986;Margolis et al 1992). However, other studies have shown that much of the increase simply reflects a shift of patients from public sites (e.g., public health departments and community health clinics) to private physicians' offices (Long, Settle, and Stuart 1986;Wade 1992;Cohen and Cunningham 1993;Baker and Royalty 1997;Gruber, Adams, and Newhouse 1997).…”
Section: Previous Researchmentioning
confidence: 99%
“…Several studies have found significant positive correlations between relative Medicaid fees and both Medicaid participation and caseloads among office-based physicians in general (Sloan, Mitchell, and Cromwell 1978;Hadley 1979;Held and Holahan 1985;Mitchell 1991;Adams 1994) and pediatricians in particular (Perloff, Kletke, and Neckerman 1986;Margolis et al 1992). However, other studies have shown that much of the increase simply reflects a shift of patients from public sites (e.g., public health departments and community health clinics) to private physicians' offices (Long, Settle, and Stuart 1986;Wade 1992;Cohen and Cunningham 1993;Baker and Royalty 1997;Gruber, Adams, and Newhouse 1997).…”
Section: Previous Researchmentioning
confidence: 99%
“…First, it is not clear whether a 10 percent bonus on Medicare payments is sufficient to attract or retain physicians in HMSAs (242). Although physicians have been found to respond to increased Medicare and Medicaid reimbursement by accepting more Medicare and Medicaid patients or by providing increased care to patients they already see (161,266,395,508,564), the strength of the incentive will vary depending on the Medicare or Medicaid caseload of the physician. The increase in payment rates should result in increased income for many physicians, however.…”
Section: Medicare Bonus Paymentsmentioning
confidence: 99%
“…I apply the Sloan, Mitchell, and Cromwell (1978) model of a mixed economy with private and public payers to this question and predict that physicians affected by the implementation of SCHIP should decrease the quantity of medical services they provide and increase their participation in the public insurance program. This results from the fact that, for a portion of the physicians who were not previously participating in the public insurance program, the implementation of SCHIP changes the marginal patient from one covered by private insurance to one covered by the lower-reimbursing government program.…”
Section: Introductionmentioning
confidence: 99%